1974
DOI: 10.1002/art.1780170504
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic reactivity in rheumatoid arthritis response to mitogens

Abstract: The in vitro responsiveness of peripheral blood lymphocytes to a variety of mitogens was compared in cells from normal volunteers, from patients with rheumatoid arthritis and from patients with degenerative joint disease (osteoarthritis). A consistent and marked depression in the proliferative response to Conconavalin A was noted, while statistically comparable results were obtained with PHA and allogeneic lymphocytes. The significance of these observations is discussed with particular reference to a possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
1

Year Published

1976
1976
1979
1979

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 13 publications
3
9
1
Order By: Relevance
“…One of these studies found no evidence for independence of response between PHA and Con A (14). The other study, by Lance and Knight (15), yielded data that compare very closely with data from the present study and those authors suggest an interpretation very similar to the one proposed here.…”
Section: Discussionsupporting
confidence: 92%
“…One of these studies found no evidence for independence of response between PHA and Con A (14). The other study, by Lance and Knight (15), yielded data that compare very closely with data from the present study and those authors suggest an interpretation very similar to the one proposed here.…”
Section: Discussionsupporting
confidence: 92%
“…The decreased proliferative response of peripheral blood lymphocytes from RA patients to virus antigens which was demonstrated in the present study extends previous reports of diminished cellular immunity in RA (19)(20)(21)(22)(23)(24)28). Significantly fewer RA patients than controls responded to measles, rubella, and parainfluenza types 2 and 3 antigens, and the magnitude of response was significantly lower to rubella and parainfluenza types 1,2, and 3.…”
Section: 1 2 3 4 5 6supporting
confidence: 87%
“…In one study (12) R A synovial cells were observed to be less susceptible than other synovial cells to growth of rubella, a finding that suggests prior virus infection, but others (9.13.14) have not confirmed that observation. Although the studies mentioned here suggest a possible role for viruses in the pathogenesis of RA, numerous attempts to culture viruses from various tissues and fluids from R A patients have been unsuccessful Diminution of cell-mediated immunity in R A has been indicated by decreased responses in vitro to plant mitogens (19)(20)(21) and in vivo to skin test antigens (22,23) and by low levels of circulating thymus-dependent (T) lymphocytes (24) although conflicting results have been reported (25-27). A recent study (28) demonstrated a correlation between decreased response to mitogens and erosive R A , indicating an association with more advanced disease which could explain the varied results among studies from different laboratories.…”
mentioning
confidence: 99%
“…Most of rheumatoid plasmas inhibited the lymphocyte response to PHA, which agrees with the report by Lance and Knight [18] but could be in conflict with the reports by Waxman et al [19] or Horwitz et al [20] who did not observe significant suppressive effect of rheumatoid sera on the lymphocyte response to PHA. Such discrepant results could be explained by a difference of meth ods used and a variability of the tests.…”
Section: Discussioncontrasting
confidence: 54%